Challenges and Adaptation Strategies of Mosque Takmirs in the Transition from Conventional Reporting to Accounting Standards Based on PSAK 45 and PSAK 101 - Rakhmawan Habibi; Zakiyyah Ilma Ahmad; Mohamad Nur Husen; Nur Laily Hidayati (ISTIFADA : Jurnal Ekonomi dan Lembaga Keuangan Syariah, 2026)
Modernizing mosque financial governance toward accountable accounting standards is a necessity in the era of digital disruption and increasing demands for public transparency. However, the transition process is fraught with complex organizational challenges. This study aims to identify key challenges and formulate effective adaptation strategies for mosque administrators in the transition process from a conventional cash-based reporting system to the implementation of Financial Accounting Standards Statement (PSAK) 45 and PSAK 101. This study uses a qualitative approach with conceptual analysis based on a synthesis of literature on change management, non-profit accounting, and studies of religious organizations, and is analyzed using Lewin's theory of change framework. The results identify three broad categories of interrelated challenges: cultural (worship vs. management paradigm and personal belief-based culture), competency (low accounting literacy among mosque administrators), and structural (lack of change leadership and resource allocation). An in-depth analysis of the interaction of these challenges yields a new finding : a Mosque Governance Adaptation Strategy Framework (SATKAM) . This framework is a three-stage change management model—Unfreeze, Change, and Refreeze—containing a series of practical and replicable strategies. These findings make a significant contribution by offering a managerial roadmap that transforms the discourse from what to achieve to how to achieve it , thus serving as a guide for administrators and stakeholders in managing the change process in a more structured and effective manner